2021
DOI: 10.1186/s12887-021-02679-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on childhood Mycoplasma pneumoniae infection in Chengdu, China

Abstract: Background Following the outbreak of the COVID-19 pandemic, a change in the incidence and transmission of respiratory pathogens was observed. Here, we retrospectively analyzed the impact of COVID-19 on the epidemiologic characteristics of Mycoplasma pneumoniae infection among children in Chengdu, one of the largest cities of western China. Method M. pneumoniae infection was diagnosed in 33,345 pediatric patients with respiratory symptoms at the Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 36 publications
7
18
0
Order By: Relevance
“…It is unclear whether this finding is due to the epidemiological characteristics of MP itself or the impact of public interventions. This result is also in agreement with the findings of Zhang et al ( 3 ) who assessed cases of MP infections in Chengdu, China, every month from January 2017 to December 2020, and found that limiting close contact reduced the transmission of MP. It was confirmed that public-intervention measures can effectively reduce MP infection rates.…”
Section: Discussionsupporting
confidence: 93%
“…It is unclear whether this finding is due to the epidemiological characteristics of MP itself or the impact of public interventions. This result is also in agreement with the findings of Zhang et al ( 3 ) who assessed cases of MP infections in Chengdu, China, every month from January 2017 to December 2020, and found that limiting close contact reduced the transmission of MP. It was confirmed that public-intervention measures can effectively reduce MP infection rates.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to 2019, the total positive rate of atypical pathogens decreased in 2020, with an emphasis on the positive rate of MP detection from 32.9% to 21.5%. This was consistent with previous results obtained in other regions of China ( Li et al., 2021 ), in which the number of positive MP cases significantly decreased in 2020 for the public health response to COVID-19 ( Zhang et al., 2021b ). The positive rate of CP among children with acute respiratory infection decreased from 0.9% in 2019 to 0.3% in 2020, which was significantly lower than that of MP infection.…”
Section: Discussionsupporting
confidence: 93%
“…This may be because the number of MP -positive patients did not decrease as fast as the total number of hospitalizations. The numbers of MP -positive patients and the total number of hospitalizations from March to December 2020 were obviously lower than those in 2019, which was consistent with previous results found in Chengdu, China ( Zhang et al., 2021b ). Although the positive rate of CP was low in both 2019 and 2020, the number of CP -positive patients monthly in 2020 was still significantly decreased compared with that in 2019.…”
Section: Discussionsupporting
confidence: 90%
“…Data from some countries during the first months in 2020 indicated that the introduction of NPIs also coincided with a reduction in Mycoplasma pneumoniae detections [ 2 , 6 , 10 ]. Mycoplasma pneumoniae is a major bacterial cause of respiratory tract infections in children and adults [ 11 ].…”
Section: Introductionmentioning
confidence: 99%